Effect of Perception for Organisational Politics on Employee Engagement with Personality Traits as Moderating Factors - Jain, Lalita; Ansari, Abdul Aziz (UI Scholars Hub, 2018)
Organisational politics affect almost every employee to some degree, becoming an inevitable and significant part of the entire organisation. Employees who feel victimised by office politics generally develop negative behaviours towards work and the entire organisation, affecting their performances. Differences in personality dimensions cause employees to demonstrate various responses to similar situations. This study assesses whether the perception of organisational politics affects the work and job engagement level of employees, and whether different personality dimensions moderate this relationship. Quantitative research was conducted on employees at the middle or upper level of management, working in different organisations that manufacture products in India. To collect the data, 450 structured questionnaires were distributed; 388 completed questionnaires were received and utilised for the analysis. The study concludes that a perception of organisational politics does exist among employees working in different organisations, and it has a negative relationship with both work and Organisational Engagement. Particular personality traits affect levels of engagement and act as moderators. If management wants to engage their employees more within the job and organisation, it must control the politics that create a negative perception of the organisation among employees.